The phenomenon of bullying: a comparative study of Spain and Finland - Mauri Medrano, Marta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
The article focuses on comparing two approaches in bullying prevention: the one in Aragon (Spain) with the one in Finland. The Finnish KiVA method is very new and can bring about great progress in detecting and dealing with bullying. The KiVA programme consists of lessons and work done during a course of study. Depending on the level of education, an educational unit will consist of a talk on how to respect others and how to work in a group. The most essential aspect of it is that the pupils understand the importance of preventing and stopping bullying. In this way, instead of supporting the bully, pupils would support the victim, thus conveying that they do not agree with bullying actions. Other methods focus only on the victim and the bully, but the Kiva programme emphasises involving and educating all peers and observers.

W artykule tym skoncentrowano się na porównaniu dwóch podejść do zapobiegania i działania w zakresie zjawiska bullyingu: podejścia stosowanego w Aragonii (Hiszpania) z podejściem stosowanym w Finlandii. Fińska metoda KiVA jest metodą nową i może stanowić duży postęp w wykrywaniu i radzeniu sobie z bullyingiem. Program KiVA jest cyklem spotkań lekcyjnych, w ramach których w zależności od poziomu nauczania realizuje się określone scenariusze. Rozmawia się o tym, jak szanować innych, jak pracować w grupie. Najistotniejsze jest to, aby uczniowie zrozumieli, jak ważne jest zapobieganie bullyingowi i jego powstrzymywanie. W ten sposób zamiast wspierać dręczyciela, będą oni wspierać ofiarę, dając tym samym do zrozumienia, że nie zgadzają się na takie działania. Inne metody skupiają się tylko na ofierze i dręczycielu, a w programie KiVA kładzie się nacisk na zaangażowanie i edukację wszystkich rówieśników i obserwatorów.
Występowanie zjawiska bullyingu w Hiszpanii i Finlandii – analiza porównawcza
Keywords: bullying; classroom; KiVa method; victim; aggressor; klasa szkolna; metoda KiVA; ofiara; agresor